PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SENI RUPA PADA MATA PELAJARAN SENI BUDAYA SISWA KELAS VII SMPN 15 PADANG - ZELVIA NORA, Drs. Wisdiarman, M.Pd, Dr. Ramalais Hakim, M.Pd (Serupa The Journal of Art Education, 2014)
This research aims to determine the effect of cooperative learning model type of Student Teams Achivement Division ( STAD ) on learning outcomes Seni Rupa class VII in SMP 15 Padang . hypothesis tested in this research is the result of learning Seni Rupa class VII in SMP 15 Padang who taught using cooperative learning model Student Teams Achivement Division ( STAD ) differ significantly from the results of studying Seni Rupa, students who taught using conventional learning models .Type of study is a quasi-experiment using research designs prretest - posstest control group design . population in this study were all students of class VII in SMP 15 Padang school year 2013/2014 and sampling techniques are students of class VII – 6 as ( experimental class ) and class VII - 5 as ( grade control ) . Data were collected by achievement test . Data were analyzed by t-test.Based on the above research findings , it can be concluded that the use of cooperative learning model type of Student Team Achivement Division differently to learning outcomes of students taught using conventional learning model in Seni Rupa classes VII in SMP 15 Padang . Therefore cooperative learning model type of Student Teams Achivement Division ( STAD ) is very good for improving student learning outcomes , especially in learning Seni Rupa class VII in SMP 15 Padang.